Number of Super Rich People, State Officials Wealth Report Compliance Level of Indonesian Officials - Junaedi Junaedi (FKIP, Universitas Palangka Raya, 2024)
The Wealth Report 2022 by Knight Frank, states that the number of people with ultra-high net worth individuals (UNWHI) in Indonesia had reached 1,403 people. In contrast, the number of super-rich people in Indonesia has increased 68% since 2016 when it was recorded at only 832 people.The richest official in Indonesia, Minister of Tourism and Creative Economy, followed by Prabowo Subianto, Nadiem Anwar Makarim, Luhut Binsar Pandjaitan, and Airlangga Hartarto. Meanwhile, the status of the State Administrator's Wealth Report (LHKPN) for 5 (five) other officials is still in the verification process, namely Tahir, Muhamad Mardiono, Benny Laos, Wiranto, and Muhidin, for Echelon I officials, this was achieved by Suryo Utomo, an employee of the Ministry of Finance.The level of LHKPN compliance in various Ministries, officials, both executive, legislative and judicial, namely: In the Republic of Indonesia Ministry environment, the highest was achieved by the Ministry of Health, namely 89.45%, while the lowest LHKPN Compliance was completed by the Coordinating Ministry for Political, Legal and Security Affairs (Coordinating Ministry for Political, Legal and Security Affairs), namely only 40.22%.